2020
DOI: 10.2478/aut-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Sewing Thread Consumption for Different Lockstitches of Class 300 Using Geometrical and Multi-Linear Regression Models

Abstract: This paper aims to provide rapid and precise methods to allow industrials to predict the amount of sewing thread needed to sew a garment using different lockstitches of class 300 (301, 301/301, 304, 308, 309, 310, 311, 312, and 315). To avoid unused stocks for each stitch type, a sewing consumption value was determined using a geometrical method of different lockstitch shapes. Furthermore, the relationships between overall geometrical models of the studied lockstitches of class 300 were developed. Indeed, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The very basic equations for thread consumption based on the seam geometry have been given long back for lockstitch 301 by assuming a rectangular seam profile (Davis, 1933), where the geometry of seam was simply defined by the length of stitch and the fabric thickness. Most of the geometrical models available for thread consumption prediction are based on rectangular profiles (Ghosh and Chavhan, 2014;Jaouadi et al, 2006), the geometrical model proposed (Rasheed et al, 2014;Sarah et al, 2020) based on the rectangular profile with further consideration of the space covered by thread interlacement point and the thickness in terms of the fabric diameter. It was observed that all the geometrical models showed more error in prediction of thread consumption; this may be because of the consideration of rectangular profile shape of the seam and other unrealistic assumptions such as cylindrical nature of the yarn and the fabric RJTA 26,4 is incompressible.…”
Section: Introductionmentioning
confidence: 99%
“…The very basic equations for thread consumption based on the seam geometry have been given long back for lockstitch 301 by assuming a rectangular seam profile (Davis, 1933), where the geometry of seam was simply defined by the length of stitch and the fabric thickness. Most of the geometrical models available for thread consumption prediction are based on rectangular profiles (Ghosh and Chavhan, 2014;Jaouadi et al, 2006), the geometrical model proposed (Rasheed et al, 2014;Sarah et al, 2020) based on the rectangular profile with further consideration of the space covered by thread interlacement point and the thickness in terms of the fabric diameter. It was observed that all the geometrical models showed more error in prediction of thread consumption; this may be because of the consideration of rectangular profile shape of the seam and other unrealistic assumptions such as cylindrical nature of the yarn and the fabric RJTA 26,4 is incompressible.…”
Section: Introductionmentioning
confidence: 99%